Education System in Pakistan: Lessons Learned and the Way Forward. (The Pakistan Development Review, 2009)
After six decades of its existence, Pakistan finds itself in an educational quagmire. There is not much to show in terms of national, provincial and local indicators of a standard variety. At the international level, the country has earned the notoriety of being regularly lower down on all known indices and league tables on human development, competitiveness and governance. Neglect of education lies at the heart of the problem. This is surprising because the thinking on the nature of the educational system required for the newly emerging country had started quite early. An All Pakistan Educational Conference was held on November 27, 1947 in Karachi. Education thus was the subject of the very first professional conference held in the country, bringing together all the stakeholders. The Father of the Nation set the guidelines in his detailed message: “Under foreign rule for over a century, in the very nature of things, I regret, sufficient attention has not been paid to the education of our people, and if we are to make any real, speedy and substantial progress, we must earnestly tackle this question and bring our educational policy and programme on the lines suited to the genius of our people, consonant with our history and culture and having regard to the modern conditions and vast developments that have taken place all over the world” [Tahir (1980), p.39]. Throughout his political career, Jinnah championed the cause of education. A number of critical issues which continue to bedevil the educational planners of Pakistan to this day, were identified by him long before the freedom struggle for Pakistan came to fruition. These include compulsory elementary education, nonelitist education, technical and vocational education for school leavers, merit-based higher education, equal opportunities for women, and adequate resourcing [Tahir (2002)]. The order of national priorities for him was education, economic development and then defence. The record of performance since independence shows a reversal of these priorities [Tahir (2008)]. Far from the welfare state envisaged by him, Pakistan has become an incorrigible security state. There are thus many lessons that have not been learned. This paper has space to focus only a few.